Clinically significant maternal X chromosomal copy number variation detected by noninvasive prenatal test. Issue 9 (19th June 2019) - Kim, Seung‐Chul; Cha, Dong‐Hyun; Jeong, Hae‐Ryun; Lee, Junnam; Jang, Ja‐Hyun; Cho, Eun‐Hae
Abstract: Maternal copy number variation (CNV), especially at the X chromosome is an important cause of false positive noninvasive prenatal test (NIPT) results for sex chromosomal aneuploidy. In addition, some maternal CNV can cause significant anomalies if the male fetus was inherited the X chromosome with CNV. During 1000 high risk Korean NIPT, we incidentally detected two cases of maternal X chromosomal CNV which can cause abnormal phenotype in a male fetus. The first false‐positive NIPT case (47, XXY) was due to a maternal 0.5 Mb duplication at Xq28, including the MECP2 gene. The second is a case of an 8‐Mb deletion on maternal Xq24q25, including GRIA3 and XIAP genes.